Detection of viral agents associated with Porcine Respiratory Disease Complex (PRDC) in pigs in North Kerala - Jayanth Kolar Venkatachalapathi; Shashank Somashekara; Rajasekhar Ravindran; Ajith Jacob George; Sumod Kanjirakkuzhiyil; Madhanraj Nallusamy; Sri Ramya Lakamana; Koshy John (Journal of Veterinary and Animal Sciences)
In pigs, stress factors such as pathogenic infections, environmental conditions, and various managemental practices can lead to a disease condition known as Porcine respiratory disease complex (PRDC). The main viral agents associated with this condition are Porcine circovirus 2 (PCV2), Porcine reproductive and respiratory syndrome virus (PRRSV), swine influenza virus (SIV), porcine respiratory coronavirus (PRCV), and pseudorabies virus. A study was undertaken to assess whether PCV2 and PRRSV, alone or in combination, are present in cases of respiratory ailments of pigs in North Kerala. The presence of PCV2 was detected by polymerase chain reaction (PCR) targeting the open reading frame 2 (ORF2) of the virus and PRRSV was detected by reverse transcriptase PCR (RT-PCR) targeting ORF6. A total of 54 tissue and lung samples were collected and screened for the presence of PCV2 and PRRSV. Of the samples tested, PCV2 could be detected in 22 (40.74 %) and PRRSV could be detected in 13 (24.07 %) samples. Two tissue samples showed mixed infections with PCV2 and PRRSV. The result shows that viral agents associated with PRDC are prevalent in pigs in North Kerala and that coinfections are also present. Keywords: Porcine respiratory disease complex, Porcine circovirus 2, Porcine reproductive and respiratory syndrome virus, polymerase chain reaction